Feasibility and economic assessment of chromocolonoscopy for detection of proximal serrated neoplasia within a population-based colorectal cancer screening programme (CONSCOP): an open-label, randomised controlled non-inferiority trial. (May 2019) - Hurt, Chris; Ramaraj, Rajeswari; Farr, Angela; Morgan, Meleri; Williams, Namor; Philips, Ceri J; Williams, Geraint T; Gardner, Georgina; Porter, Catherine; Sampson, Julian; Hillier, Sharon; Heard, Hayley; et al.
Summary: Background: Most post-colonoscopy interval colorectal cancers are proximal; serrated polyps are often precursors to these cancers and are considered difficult to detect. We assessed the safety, feasibility, and economic effect of chromocolonoscopy on detection of proximal serrated neoplasia. Methods: We did an open-label, multicentre, randomised, controlled non-inferiority trial including patients from Bowel Screening Wales centres. Participants who tested positive for faecal occult blood and who were eligible for and considered fit to have colonoscopy (patients with known cases of polyposis syndromes, Lynch syndrome, and chronic inflammatory disease were excluded) were randomly assigned (1:1; with the use of minimisation, stratified by centre with an 80:20 random element) to either standard white light colonoscopy (standard group) or chromocolonoscopy (indigo carmine dye [0·2%]; chromocolonoscopy group) using a secure, internet-based, computerised, randomisation system that used centralised, dynamic allocation. Participants were followed up for 1 year and data from index colonoscopies and associated clearance procedures were analysed. All proximal polyps were reviewed by an expert pathologist panel. The main outcome on which power was based was time taken to perform the colonoscopy procedure, defined as from the time when the scope was inserted to withdrawal from the anus, assessed in the per-protocol population. The non-inferiority margin was 15 min. This trial is complete and is registered withClinicalTrials.gov, numberNCT01972451 . Findings: Between Nov 20, 2014, and June 16, 2016, 741 (72%) of 1031 patients screened were eligible and consented: 360 were randomly assigned to white light colonoscopy and 381 to chromocolonoscopy. In the chromocolonoscopy group, the procedure took a mean of 36·8 min (SD 15·0), compared with a mean of 30·6 min (13·7) in the standard group (mean difference 6·3 min [95% CI 4·2–8·4] longer with chromocolonoscopy than in the standard group). The mean difference was within the prespecified non-inferiority margin. Detection rates for proximal serrated lesions were significantly higher in the chromocolonoscopy group than in the control group (45 [12%] of 381 patients vs 23 [6%] of 360 patients; odds ratio 1·96 [95% CI 1·16–3·32]; p=0·012). Serious adverse events (four cases of postpolypectomy bleeding [two in each group], and one case of anxiety and hyperventilation [in the chromocolonoscopy group]), colonoscopy quality measures, comfort scores, and sedation were similar between groups. Interpretation: Chromocolonoscopy is feasible within a population-based colorectal cancer screening programme, is safe, and has significantly increased detection of proximal serrated neoplasia and other polyp types compared with standard colonoscopy. Larger randomised trials of chromocolonoscopy, powered for improved detection of significant serrated polyps and for longer-term follow-up to investigate the effect on reduction of interval cancers within screening populations, are warranted. Funding: Health and Care Research Wales (RfPPB–1021).